The Transformation of E-government Through The Regional Government Information System (SIPD) at The Regional Human Resource Development Agency of South Sumatra Province: Transformasi E-Government Melalui Sistem Informasi Pemerintahan Daerah (SIPD) di Badan Pengembangan Sumber Daya Manusia Daerah Provinsi Sumatera Selatan - Farhan Fasha Syuhada; Julian, Christofer; Iriani , Atrika; Chairani, Annisa Larasati; Austin, Trecy (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study discusses the transformation of e-Government through the implementation of the Regional Government Information System (SIPD) at the Regional Human Resource Development Agency (BPSDMD) of South Sumatra Province. The purpose of this research is to analyze how SIPD implementation improves efficiency, transparency, and accountability in regional financial management, as well as to identify the challenges faced during its implementation. The method used is a qualitative approach with data collection techniques including interviews, observation, and document analysis. The results show that SIPD enhances efficiency in planning and budgeting processes, and improves data integration. However, challenges such as technological infrastructure limitations and human resource readiness remain obstacles. The conclusion of this study is that SIPD implementation at BPSDMD South Sumatra contributes to better governance, but requires improvements in human resource competencies and technology infrastructure reinforcement.